MODERN OPPORTUNITIES FOR IMPLEMENTING OBSERVATION AND ANALYSIS IN DETERMINING THE EFFECTIVENESS OF TEACHERS' ACTIVITIES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS - Fayziyeva Mabudakhon Mukhammadjonovna (Web of Journals Publishing, 2025)
Monitoring and analyzing the effectiveness of teachers in preschool educational institutions is an important component of ensuring high-quality education for early childhood. This article examines modern opportunities and strategies for assessing and improving the performance of educators in preschool educational institutions. By exploring innovative monitoring methods, data analysis tools, and the foundations of performance evaluation, this article aims to provide insights into improving teaching practices, promoting professional development, and optimizing educational outcomes for early childhood education.
Keywords: Teacher effectiveness, Preschool education, Monitoring, Analysis, Performance evaluation, Professional development